Global Reporting Initiative and its implementation in Bulgarian and Ukrainian enterprises - Nikolov, E. (Економічний вісник Донбасу, 2016)
The activity of business organizations, mostly large multinationals, attracts the attention of an increasing part of the society. Such interest cannot be satisfied with the information provided in the traditional financial and accounting reports; as a result, due to the pressure of social expectations, business organizations have started to publish non-financial information in the so called corporate social reports, also called sustainability reports or corporate society reports. Although they do not have regulated content, the Global Reporting Initiative has been adopted as a global reporting standard as of today. In this respect, the purpose of this article is to investigate GRI’s reporting structure among Bulgarian and Ukrainian business organizations on the basis of which it will outline the principal problematic areas as well as the existing differences among them. Діяльність бізнес-організацій і, насамперед, великих мультинаціональних корпорацій, викликає інтерес все більшої частини суспільства. Його не можна задовольнити за допомогою інформації, що міститься у традиційній бухгалтерській фінансовій звітності, у результаті чого під тиском суспільних очікувань господарські організації почали публікувати нефінансову інформацію в корпоративних соціальних звітах, які ще називають звітами про сталий розвиток або про корпоративне громадянство. Незважаючи на те, що вони не мають регламентованого вмісту, в якості глобального стандарту у звітності ствердилася структура Global Reporting Initiative. У зв'язку з цим мета цієї статті - дослідити поширення структури звіту GRI серед болгарських і українських бізнес-організацій і на цій базі окреслити основні проблемні сектори, а також виявити існуючі відмінності між ними. Деятельность бизнес-организаций и, прежде всего, крупных мультинациональных корпораций вызывает интерес все большей части общества. Его нельзя удовлетворить посредством информации, содержащейся в традиционной бухгалтерской финансовой отчетности, в результате чего под давлением общественных ожиданий хозяйственные организации начали публиковать нефинансовую информацию в корпоративных социальных отчетах, называемых еще отчетами об устойчивом развитии или о корпоративном гражданстве. Несмотря на то, что они не имеют регламентированного содержания, в качестве глобального стандарта в отчетности утвердилась структура Global Reporting Initiative. В этой связи цель настоящей статьи - исследовать распространение структуры отчета GRI среди болгарских и украинских бизнес-организаций и на этой базе очертить основные проблемные сектора, а также выявить существующие различия между ними.